PENGARUH LIKUIDITAS TERHADAP HARGA SAHAM DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL INTERVEENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Maylah, Maylah; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This research aims to analyze and test the effect of liquidity on stock prices with Financial distress as an intervening variable in Property and Real Estate Companies listed on the Indonesia Stock Exchange for the period 2018-2020. This research is a descriptive research. The population in this study are all Property and Real Estate Companies listed on the IDX for the period 2018-2020. The sampling technique in this research is using purposive sampling and sample in this study amounted to 33 financial statements. The analysis technique usedis the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test, Liquidity has a significant positive effect on Financial distress, Liquidity has a significant positive effect on Stock prices, Financial distress has a significant negative effect on Stock prices. Liquidity variable on Stock prices through Financial distress has a significant positive effect.